SCIENTIFIC AND METHODOLOGICAL BASESS OF STANDARDIZATION OF LOADS IN PHYSICAL TRAININGAND MASS SPORTS HEALTH TRANING (Academicia Globe: Inderscience Research, 2022)
In this article, we will talk about the importance of normalizing loads in physical education and mass sports-wellness training.